Cemilan Sehat Ibu Hamil “Biskuit Jantung Pisang” sebagai Pencegahan Stuting di Kecamatan Mariso Kota Makassar - Muhammad Thabran Talib; Lilik Meilany; Novi Puspita Sari (Syntax Corporation Indonesia, 2024)
Mariso Village is one of the working areas of Puskesmas Dahlia that faces nutrition challenges, especially stunting. In addition, pregnant women also need special attention to their nutritional intake, because lack of nutrition during pregnancy can be one of the main causes of stunting. Based on data collected by 25 posyandu cadres spread throughout the hamlet, there are 14 children with stunting conditions and 6 pregnant women who experience Chronic Energy Deficiency (CEC). Puskesmas Dahlia has run a nutrition kitchen program as an effort to handle stunting in children. However, there are obstacles in utilizing the available local food ingredients, and some programs have not covered pregnant women. In the context of community service, efforts were made to educate posyandu cadres about stunting, SEZ in pregnant women, and the utilization of local ingredients such as banana heart, one of which was through the innovation of making Banana Heart Biscuits “BINTANG”. Various methods were applied in this activity, including initial observation in the form of measuring children's weight (BB) and height (TB), and measuring the upper arm circumference (LILA) of pregnant women. The activity continued with health education for posyandu cadres and a demonstration of banana heart-based biscuit making. Initial observations conducted over two days showed that there were 14 stunted children and 6 SEZ pregnant women. After that, health education was provided to cadres, followed by training in biscuit making, as well as assistance and product distribution by cadres. The results of this activity increased the knowledge of posyandu cadres while positively impacting the nutritional status of stunted children and pregnant women with SEZ. Banana Heart Biscuits are now one of the additional menus provided in posyandu activities for toddlers and pregnant women. In addition, these biscuits are also used as a side menu in the Supplementary Feeding program which is routinely held every week in Bontorannu Village.